2001
DOI: 10.1054/bjoc.2001.1727
|View full text |Cite
|
Sign up to set email alerts
|

The bisphosphonate, zoledronic acid, induces apoptosis of breast cancer cells: evidence for synergy with paclitaxel

Abstract: SummaryBisphosphonates are well established in the management of breast-cancer-induced bone disease. Recent studies have suggested that these compounds are effective in preventing the development of bone metastases. However, it is unclear whether this reflects an indirect effect via an inhibition of bone resorption or a direct anti-tumour effect. The breast cancer cell lines, MCF-7 and MDA-MB-231 cells were treated with increasing concentrations of the bisphosphonate, zoledronic acid, for varying time periods,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
222
4
9

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(254 citation statements)
references
References 25 publications
19
222
4
9
Order By: Relevance
“…We showed here that this relatively low concentration was able to block growth factors' effects, and to inhibit the 'protective' effect of growth factors on breast cancer cell survival. The effects of bisphosphonates that we observed were thus obtained with relatively low concentrations of bisphosphonates, in contrast to earlier works that reported the requirement for higher concentrations, between 20 and 1000 mM, to exhibit antitumour effects (Senaratne et al, 2000;Lee et al, 2001;Jagdev et al, 2001a).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We showed here that this relatively low concentration was able to block growth factors' effects, and to inhibit the 'protective' effect of growth factors on breast cancer cell survival. The effects of bisphosphonates that we observed were thus obtained with relatively low concentrations of bisphosphonates, in contrast to earlier works that reported the requirement for higher concentrations, between 20 and 1000 mM, to exhibit antitumour effects (Senaratne et al, 2000;Lee et al, 2001;Jagdev et al, 2001a).…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, clodronate and pamidronate are bisphosphonates of first/second generations. In contrast, ibandronate and zoledronic acid are last generation bisphosphonates that represent the two most potent compounds (Hiraga et al, 2001;Jagdev et al, 2001a;Rosen et al, 2001;Body, 2003;Lipton, 2003). Despite their marked differences in potency to inhibit bone resorption in vitro or in vivo, we did not observe major differences between the potency of these four compounds in our in vitro experiments.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…A recent study using an in vitro model of cell invasion has also suggested that BPs may inhibit the early event in the formation of bone metastases (Boissier et al, 2000). Furthermore, several investigations have reported the inhibition of cell growth and cell survival by BPs on breast cancer cells (Fromigue et al, 2000;Senaratne et al, 2000;Hiraga et al, 2001;Jagdev et al, 2001).…”
mentioning
confidence: 99%